2018
DOI: 10.3389/ffgc.2018.00010
|View full text |Cite
|
Sign up to set email alerts
|

Understory Vegetation in Oil Palm Plantations Benefits Soil Biodiversity and Decomposition Rates

Abstract: Oil palm is the most productive vegetable oil crop per unit area and is crucial to the economy of developing countries such as Malaysia and Indonesia. However, it is also highly controversial due to the impact it has on biodiversity. Inputs of herbicides to control understory vegetation in plantations are high, which is likely to harm native biodiversity, but may be unnecessary in protecting oil palm yield. In this study we investigate the effects of understory manipulation using herbicides on soil fauna, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 61 publications
(77 reference statements)
3
71
0
Order By: Relevance
“…The effect was stronger for small cryptic soil-associated spiders, suggesting that they predominantly suffer from the loss of litter shelter. A positive effect of understory density and height on density and diversity of soil-associated and litter-associated spiders supports other studies showing that complex ground vegetation promotes ground invertebrate communities in plantations (Ashton-Butt et al 2018). Unlike taxonomic and functional diversity, predation by spiders was affected rather by plant diversity than habitat structure.…”
Section: Predation Loss In Litter and Soilsupporting
confidence: 87%
“…The effect was stronger for small cryptic soil-associated spiders, suggesting that they predominantly suffer from the loss of litter shelter. A positive effect of understory density and height on density and diversity of soil-associated and litter-associated spiders supports other studies showing that complex ground vegetation promotes ground invertebrate communities in plantations (Ashton-Butt et al 2018). Unlike taxonomic and functional diversity, predation by spiders was affected rather by plant diversity than habitat structure.…”
Section: Predation Loss In Litter and Soilsupporting
confidence: 87%
“…increased vegetation could also prevent soil degradation and aid regeneration of SOM (Ashton-Butt et al, 2018) as seen in other crops (Keesstra et al, 2016;Parfitt et al, 2010). We recognize that due to the relatively coarse level of identification of soil macrofauna in this study, more nuanced relationships of diversity and community composition change between oil palm ages may have been missed.…”
Section: Change In Soil Macrofauna Composition After Replantingmentioning
confidence: 90%
“…Soil monoliths were taken from both the weeded circle and the windrow of each palm (see Ashton-Butt et al, 2018;Carron et al, 2015). Soil monoliths were taken from both the weeded circle and the windrow of each palm (see Ashton-Butt et al, 2018;Carron et al, 2015).…”
Section: Sampling Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In oil palm plantations, habitat complexity has been implemented by preserving forest patches, preserving and creating riparian buffers, and by enhancing understory vegetation (Lucey et al, 2014;Luke et al, 2018). The latter can grow up to several meters tall in mature oil palm plantations (Tan, Kanniah, & Cracknell, 2014), and studies have shown that maintaining understory vegetation encourages plant, invertebrate and vertebrate biodiversity (Ashton-Butt et al, 2018;Luke, Purnomo, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%